Analysis and diagnosis of the reality of marketing intelligence in Iraqi banks Analytical and diagnostic study in selected banks in Kirkuk (Journal of Humanities and Social Sciences Research, 2023)
The study aims to analyze and diagnose the reality of marketingintelligence in Iraqi banks with its four dimensions (customerunderstanding, market understanding, product intelligence, competitorsintelligence). The study was conducted on a number of banks in theprovince of Kirkuk, namely (Al-Noor Bank, One June Bank, Al-RashidBank). The size of the final sample population was (57). The researcherrelied on the statistical analysis of the data collected from the bankssurveyed. I rely on the five-point Likert scale through the questionnaire,which was designed as a means of data collection. A number ofconclusions and recommendations were reached, including that the banksunder study should give a more important character to marketingintelligence.